2017
DOI: 10.1016/j.reprotox.2017.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Fetal-sex dependent genomic responses in the circulating lymphocytes of arsenic-exposed pregnant women in New Hampshire

Abstract: Exposure to inorganic arsenic (iAs) during pregnancy is associated with adverse health outcomes present both at birth and later in life. A biological mechanism may include epigenetic and genomic alterations in fetal genes involved in immune functioning. To investigate the role of the maternal immune response to in utero iAs exposure, we conducted an analysis of the expression of immune-related genes in pregnant women from the New Hampshire Birth Cohort Study. A set of 31 genes was identified with altered expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In both states, a sizable percentage of the population has groundwater as the source of its drinking water [15,16]. Researchers associated with NIEHS-funded Environmental Health Sciences Core Centers are exploring the ways that arsenic impacts health, especially when ingested as drinking water [17,18]. Additionally, both states are home to racial/ethnic minority and rural populations, who are especially likely to experience health disparities related to contaminants in unsafe drinking water [19].…”
Section: Introductionmentioning
confidence: 99%
“…In both states, a sizable percentage of the population has groundwater as the source of its drinking water [15,16]. Researchers associated with NIEHS-funded Environmental Health Sciences Core Centers are exploring the ways that arsenic impacts health, especially when ingested as drinking water [17,18]. Additionally, both states are home to racial/ethnic minority and rural populations, who are especially likely to experience health disparities related to contaminants in unsafe drinking water [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated differences in serum corticosterone by sex, related to greater transport of corticosterone across placenta of female as compared to male fetuses. Additionally, the placental response to metals exposure, including As, has been shown to vary with the sex of the fetus (Bommarito et al, 2017; Rager et al, 2017; Winterbottom et al, 2015; Winterbottom et al, 2017). Future research should focus on mechanisms of early sex-specific variation in placental biology, as well as physiological differences in development and metabolism in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in Flint, Michigan and other cities around the United States, children are continuously exposed to metals, particularly though drinking and food sources. Lead has been a chronic problem in the United States with many children presenting with blood leads higher than 5 μg/dl (DeWitt, 2017; Hanna-Attisha et al, 2016; Shah et al, 2017) and over a 100 million people are exposed to elevated levels of arsenic (greater than 10 μg/L) through drinking sources, including well water (Bommarito et al, 2017; Organization, 2004; Rager et al, 2017; Wasserman et al, 2004; Wasserman et al, 2016). A significant public health concern surrounding metal exposure relates to their potential to produce cognitive deficits (Canfield et al, 2004; Debes et al, 2016; Jeong et al, 2017; Lanphear et al, 2005; Wasserman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…AS3MT is the major genetic factor that influences iAs metabolism; multiple other genes 72 and epigenetic factors 73 make smaller contributions. The evolutionary importance of AS3MT is supported by studies led by Karin Broberg, a professor of environmental medicine at the Karolinska Institute and Lund University, Sweden.…”
Section: Variations In Toxicitymentioning
confidence: 99%